Learning Difficulties in Islamic Jurisprudence (Fiqh): A Human-Centered Analysis of Cognitive, Instructional, and Family Support Factors in an Indonesian Islamic Senior Secondary School - Harir Jhibran; Susy Pransiska (WISE Pendidikan Indonesia, 2026)
This study analyzes students’ learning difficulties in Islamic jurisprudence (Fiqh), their interacting causes, and the instructional responses implemented at an Islamic senior secondary school in Jambi, Indonesia. Using a qualitative descriptive case study, the research involved one Fiqh teacher and purposively selected Grade 10 students. Data were collected through in-depth interviews, classroom observations, and document review, then analyzed through data condensation, thematic display, and iterative verification. The findings identify three areas of difficulty: Islamic inheritance law, commercial contracts, and Arabic legal terminology. These difficulties arose from limited conceptual readiness, uneven prior knowledge, and the cognitive demands of legal reasoning. Instructional clarity, contextual examples, visual media, a supportive classroom climate, and family encouragement reduced, but did not fully remove, these barriers. The teacher responded through scaffolded explanations, question-and-answer interaction, role modelling, religious habituation, and authentic practice. The study offers a human-centered perspective in which content complexity triggers difficulty, learner readiness shapes vulnerability, and adaptive instructional and social support improves participation. It highlights the need for differentiated, low-stigma, and context-responsive learning support